Optimization of educational activity and support of educational process at teaching on medical biology. - S. I. Dubinin; V. O. Piliuhin; A. V. Vatsenko; N. A. Ulanovskaya-Tsyba; N. O. Perederii; O. B. Ryabushko; O. V. Ovcharenko; O. V. Klepets (Морфологія, 2019)
Background. There are many options for organizing and implementing of educational activities and achieving the goal of learning. The methodological basis of optimization is a systematic approach, which requires considering all the components of training and the educational process in the unity of regular relationships, relying on the general theory of management by complex dynamic systems. Objective is to prove that optimization of teaching is possible in condition of modern methodical and technical support, that daily activity of teachers should be targeted to replenishment of training and methodical materials, applying of innovative informational technologies and effective methods of knowledge control. Methods. Medical biology is a complex science which studies structural, functional and genetic bases of human vital functions on the different levels of life organization and organisms that cause critical human conditions. With the purpose of optimization of  educational process and standartization of preparing of specialists at application of the various methodical and technical support, the teachers of the department use developed by them textbooks and manuals, collections of tests, interactive informational technologies (computer programs, multimedia support of lectures and practical classes, electronic database), which allow to teach the subject effectively, to develop the competentions and to master fundamental disciplines. Conclusion. Optimization of educational process and in particular preparing on medical biology needs the improvement of methodical and technical support, using interactive computer software and the execution of tests and situational tasks.